2017
DOI: 10.1177/0954405416684156
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of ceramic tool in intermittent turning of hardened steel

Abstract: The aim of this investigation is to identify the Al 2 O 3-(W, Ti)C ceramic fracture modes and failure mechanisms under different cutting speeds and feed rates during intermittent turning of hardened 20CrMnTi steel. The failure surfaces of the cutting tools were examined by digital optical microscope and scanning electron microscope. The cutting forces and transient temperature in the intermittent turning process were measured during the entire life cycle. The experimental results showed that the cutting forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The Vc factor comes in third place with a cont% of 10.75%, while r is nonsignificant P > 0.05 with a cont% of 0.41%. Gong et al [9] reported similar results, Cui et al [40], Ni et al [41] indicating that the increase of both factors ap and f causes the increase of effort Fz. From the ANOVA of Pm, it is obvious that all the input factors are significant; Vc and ap have the major influence, with a cont% of 40.37% and 39.93% respectively.…”
Section: Resultsmentioning
confidence: 56%
“…The Vc factor comes in third place with a cont% of 10.75%, while r is nonsignificant P > 0.05 with a cont% of 0.41%. Gong et al [9] reported similar results, Cui et al [40], Ni et al [41] indicating that the increase of both factors ap and f causes the increase of effort Fz. From the ANOVA of Pm, it is obvious that all the input factors are significant; Vc and ap have the major influence, with a cont% of 40.37% and 39.93% respectively.…”
Section: Resultsmentioning
confidence: 56%
“…However, the situation would be different when the cutting speed increased to 300 m/min, at which the cutting temperature was relatively high and the adhesive wear and diffusion wear would become serious. 26,29 Differing from the medium and low-speed machining, the effect of friction characteristics on tool life would be weak at high-speed machining free-cutting steels (300 m/min). Here, with combined action of serious adhesive wear and diffusion wear, intensified by the high cutting temperature, the tool lives would also be poor.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of cutting speed would also enhance the cutting temperature. 10,29 The slight reduction of cutting force can be attributed to the thermal softening effect of free-cutting steel materials during machining. [30][31][32] Combined with the results of tool lives (Figure 3), it seems that the rapid decrease of tool lives at the speed of 300 m/min can also be attributed to the high temperature, which can intensify the main wear behaviors, such as adhesive wear and diffusion wear.…”
Section: Tool Life and Cutting Forcementioning
confidence: 99%
“…Furthermore, the average cutting forces increased with the increase in the feed rate in the intermittent cutting hardened steels. See the literature 34 for a detailed discussion. Spatial and temporal distribution of cutting stress.…”
Section: Tool Failure Mechanism Analysismentioning
confidence: 99%